2013
DOI: 10.1002/mus.23904
|View full text |Cite
|
Sign up to set email alerts
|

SMA valiant trial: A prospective, double‐blind, placebo‐controlled trial of valproic acid in ambulatory adults with spinal muscular atrophy

Abstract: Introduction An open-label trial suggested that valproic acid (VPA) improved strength in adults with spinal muscular atrophy (SMA). We report a 12-month, double-blind, cross-over study of VPA in ambulatory SMA adults. Methods There were 33 subjects, aged 20–55 years, included in this investigation. After baseline assessment, subjects were randomized to receive VPA (10–20 mg/kg/day) or placebo. At 6 months, patients were switched to the other group. Assessments were performed at 3, 6, and 12 months. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 35 publications
3
86
0
2
Order By: Relevance
“…A small, open-label trial of valproic acid in patients with SMA types III/IV of ages 17 and older showed an increase in strength as measured by HHD in an open-label setting [39]. However, a placebo-controlled trial in adults with SMA also showed no effect, though quantitative strength testing was found to be reliable and reproducible in a trial of valproic acid in SMA [40]; results suggested no benefit but the properties of the strength assessment suggested that it would be a good measure in future trials. Similarly, a trial of type II/III SMA enrolled patients aged 6 to 36 years in a crossover study of growth hormone; HHD was again found to be reliable and reproducible, although the results suggested no effect [41].…”
Section: Quantitative Muscle Testingmentioning
confidence: 99%
“…A small, open-label trial of valproic acid in patients with SMA types III/IV of ages 17 and older showed an increase in strength as measured by HHD in an open-label setting [39]. However, a placebo-controlled trial in adults with SMA also showed no effect, though quantitative strength testing was found to be reliable and reproducible in a trial of valproic acid in SMA [40]; results suggested no benefit but the properties of the strength assessment suggested that it would be a good measure in future trials. Similarly, a trial of type II/III SMA enrolled patients aged 6 to 36 years in a crossover study of growth hormone; HHD was again found to be reliable and reproducible, although the results suggested no effect [41].…”
Section: Quantitative Muscle Testingmentioning
confidence: 99%
“…The use of HDAC inhibitors has been well advanced in the field of cancer, with many tested in clinical trials, and three approved for cancer therapy (reviewed in Mottamal et al 2015). Phase II clinical trials for the use of HDAC inhibitors for the treatment of the motor neuron disease, spinal muscular atrophy (SMA), yielded initial encouraging results, although these were not confirmed or extended by later studies (Mercuri et al 2004(Mercuri et al , 2007Swoboda et al 2010;Kissel et al 2011Kissel et al , 2014. More research on the specific targets of acetylation, the specific enzymes involved, and the development of more directed compounds are likely required.…”
Section: Establishing a Modelmentioning
confidence: 99%
“…About one-third of SMA patients are positive-responders [89]. Unfortunately, most patients do not show improvements in muscle strength or function [91]; therefore, the need for new drugs for SMA therapy effective in most patients is still urgent.…”
Section: Hdaci and Hydroxyureamentioning
confidence: 99%
“…Previously drug candidates very often failed to reproduce in SMA patients the positive effect observed in vitro or in vivo [91]. One measure to improve the preclinical studies of potential candidates was to develop more robust assays to assess the compound efficiency [113].…”
Section: Small Molecules For Splicing Correctionmentioning
confidence: 99%